Development of Culturally Responsive Teaching-Based Interactive Media to Improve Social-Emotional Skills and Learning Motivation in Primary School Students - Arini, Ririn; Rosmilawati, Ila; Hendrayana, Aan (Jurnal Paedagogy, 2025)
This study aims to develop an interactive media based on Culturally Responsive Teaching (CRT) to enhance the socio-emotional skills and learning motivation of elementary school students. The research follows the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and involves 42 students, divided into an experimental group and a control group. The instruments utilized include questionnaires, interviews, and tests. The data analysis technique in this study applies validity analysis and effectiveness analysis, measured using the N-Gain Score. The findings indicate that interactive media based on Culturally Responsive Teaching (CRT) has proven to be effective in improving elementary students’ socio-emotional skills and learning motivation, as evidenced by comprehensive N-Gain Score data. The experimental class achieved an average N-Gain Score of 0.74, whereas the control class recorded 0.29, demonstrating a high level of success in the implementation of this media. The CRT-based interactive media successfully transformed the concept of regional diversity from an abstract idea into a concrete and meaningful learning experience for students, thereby increasing their active engagement in the learning process.